The Effectiveness of Multimedia Teaching According to the Multiple Intelligences Strategy in Acquiring Social Concepts among Middle School Female Students (Journal Of Educational and Psychological Researches, 2025)
Deep understanding leads to deep learning, which uses the technology of artificial neural networks interconnected in layers of algorithms to simulate human brain capabilities and recognize complex patterns in large, multivariate datasets. The deep neural network learns from its mistakes by comparing the expected outcome with the known actual results and making adjustments to reduce prediction error. The researcher believes multimedia education has expanded the learning space and proven its effectiveness; modern applications provide opportunities to improve the education system and keep pace with development. Artificial intelligence has important and multiple roles in educational institutions, enabling them to perform efficiently.